Retrospective validation of the postnatal growth and retinopathy of prematurity criteria in a Chinese cohort - Li, Li; Gao, Yanlin; Lu, Yuhan; Chen, Wei; Han, Mei (Frontiers in Pediatrics, 2025)
PurposeTo evaluate the effectiveness and applicability of the postnatal growth and retinopathy of prematurity (G-ROP) screening criteria in a Chinese neonatal cohort.MethodsData pertaining to the retinal screening of premature infants admitted to the neonatal intensive care unit from January 2021 through December 2021 were retrospectively analyzed. The severity of ROP was graded on the basis of the International Classification of Retinopathy of Prematurity criteria established in 2005. Treatment decisions for ROP were guided by the recommendations of the Early Treatment for Retinopathy of Prematurity Cooperative Group. The presence of six key variables that comprise the G-ROP screening criteria were carefully documented. The sensitivity and specificity of the G-ROP predictive algorithm in identifying infants with ROP requiring treatment were calculated.ResultsA total of 352 infants with complete records were included in this study, among whom 120 infants (34.1%) were diagnosed with ROP. Of those, 21 infants (6.0%) received treatment. By applying the 6 criteria of the G-ROP model, all infants with severe ROP were successfully identified. The sensitivity of the G-ROP model in predicting treatment-requiring ROP was 100% (CI, 0.808–1.00), and the specificity was 47.8% (CI, 0.413–0.545). By applying the G-ROP criteria, the number of infants who required ROP screening would have been reduced by 122 (34.7%), while the number of screenings (1967) would have been reduced by 537 (27.3%).ConclusionThe prevalence of ROP (34.1%) and treatment-requiring ROP (6.0%) were relatively high in our cohort. Application of the G-ROP prediction model can improve the sensitivity and specificity of ROP screening. All infants with treatment-requiring ROP were correctly identified. The G-ROP screening criteria seemed to be effective and appropriate for predicting ROP in infants living in Tianjin, China.